Barriers to accessing termination of pregnancy in a remote and rural setting: a qualitative study. (5th May 2016) - Heller, R; Purcell, C; Mackay, L; Caird, L; Cameron, ST
Abstract : Objective: To explore the experiences of women from a remote and rural setting who had a termination of pregnancy (TOP), in relation to any barriers they may have experienced trying to access TOP. Design: Qualitative interview study. Setting: Scottish Highlands and Western Isles. Population: Women who had undergone TOP in the Scottish Highlands National Health Service between October 2014 and May 2015. Methods: Sixteen semi‐structured, audio‐recorded telephone interviews were conducted by a researcher with women who had consented to be interviewed at their initial assessment. Six stages of thematic analysis were followed to explore themes in and across participant accounts. Main outcome measures: Themes derived from interview transcripts. Results: Four themes emerged relating to barriers to access and experience: (1) the impact of travel for TOP, (2) temporal factors unique to this population and how they affected women, (3) the attitude of health professionals, notably general practitioners, as a result of local culture, and (4) stigma surrounding TOP and the expectation that abortion will be traumatising. Conclusion: Women in remote and rural areas experience barriers to accessing TOP. Prompt referrals, more providers of TOP and tackling stigma associated with TOP could make delivery of this service more equitable and improve women's journey through TOP. Tweetable abstract: Women in remote and rural areas of Scotland face multiple barriers to accessing termination of pregnancy. Tweetable abstract: Women in remote and rural areas of Scotland face multiple barriers to accessing termination of pregnancy.